Synthesis of Methyl 3-(4-hydroxyphenyl) acrylate using Domestic Microwave Irradiation at 200 Watt Power - Moch Davit Abdul Majid; Ekowati, Juni; Purwanto, Bambang Tri (Universitas Airlangga, 2023)
In this study, a methylation reaction was carried out for the p-coumaric acid compound using potassium carbonate as a base and dimethyl carbonate as a methylation agent with acetone as a solvent. The methylation reaction was carried out using microwave irradiation from microwave domestic with a power of 200 watts. The purity test was carried out on a TLC plate using three different eluents and produced a single stain that was different from the initial compound. The phenol functional group tested with FeCl3 reagent showed a positive purple color. Compound identification was done using an FT-IR spectrophotometer and a 1H-NMR spectrometer. In the synthesized FT-IR spectrum, there was an absorption of the ester group at wave numbers 1671 cm-1 (C=O group) and 1243 cm-1 (C-O group), there was a band at 3378 cm-1 indicating the presence of the phenol group. There were differences in fingerprint results in the FT-IR spectrum of the p-coumaric acid compound and the results of the methylation reaction. The 1H-NMR spectrum confirmed the presence of three methyl ester protons of the carboxylic acid and the phenolic OH. This indicated that the synthesis produced a compound, namely methyl (E)-3-(4-hydroxyphenyl) acrylate. Keywords: methyl (E) 3-(4hydroxyphenyl) acrylate), p-coumaric acid, Potasium Carbonate, Microwave Irradiation, Synthesis